Using of silicate materials for sewage sorption treatment from heavy metals - Mazurak, O.; Mazurak, A.; Marushchak, U.; Pozniak, O. (Видавництво Львівської політехніки, 2014)
The article presents the research results of using different types of silicate minerals, their modified forms for sewage sorption treatment. Their physical and chemical properties, the mechanisms of action and sorption efficiency of the widespread natural minerals are characterized in this paper. Подано результати досліджень використання різних типів силікатних мінералів, їх модифікованих форм для сорбційного очищення стоків. Охарактеризовано їх фізико-хімічні властивості, механізми дії та ефективність сорбції найпоширеніших мінералів.
Keywords: silicate; zeolites; mica; vermiculite; clays; heavy metals; isotopes; sewage; силікатні матеріали; сорбція; цеоліти; слюди; вермикуліт; глини; важкі метали; ізотопи; стічні води